The Canadian Association of Gastroenterology Education Committee Report - Ronald J Bridges (Canadian Journal of Gastroenterology)
I am pleased to provide an update regarding the activities and future directions of the Canadian Association of Gastroenterology (CAG) Education Committee. The mandate of the CAG Education Committee is to facilitate, develop and promote excellence as it pertains to educational initiatives for the Canadian gastroenterology community. Professional education has long remained a priority of the CAG - a fact well recognized by the membership. The 2002 CAG Strategic Planning Survey showed that members rate Canadian Digestive Diseases Week (CDDW) as the most important CAG service, on par with Digestive Diseases Week regarding its usefulness (1). CDDW 2004 offered delegates a variety of basic science and clinical symposia, the popular and well received 'Breakfast with the Expert' sessions and a comprehensive Postgraduate Course reviewing key developments in gastroenterology, nutrition and hepatology.